(untitled) (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines consumer protection for victims who suffer losses from unlawful or deceptive investment services under Law Number 8 of 1999 on Consumer Protection. The issue is important because illegal investment schemes often exploit low financial literacy, unrealistic promises of profit, and weak awareness of licensing and legal risk. Using normative juridical research based on statutory and library approaches, the article analyzes the position of investors as consumers, the legal certainty provided by consumer protection norms, and available mechanisms for compensation and dispute resolution. The study finds that the Consumer Protection Law provides a normative basis for legal certainty through rights, obligations, prohibitions, sanctions, and institutional complaint channels. However, implementation remains difficult because victims often face asset recovery problems, fragmented enforcement, and asymmetry of information. The article argues that effective protection requires not only formal legal certainty but also stronger preventive supervision, public education, and accessible litigation and non-litigation remedies.